THE USE OF CIRC METHOD TOWARD READING COMPREHENSION OF DESCRIPTIVE TEXT AT GRADE NINTH OF SMP NEGERI 1 GAUNG - SY.Khania Khulqi; Samsul Amri; Maizarah Maizarah (Program Studi Pendidikan Bahasa Inggris, 2019)
Reading comprehension is the process of making meaning from the texts. In this study, the students’ problems related to the students’ difficulties in gaining information from the reading texts. CIRC (Cooperative Integrated Reading Composition) method was selected to solve those problems. Thus the main purpose of this current investigation is to test whether or not CIRC brings positive effects toward the students reading comprehension of descriptive texts. This is an experimental study, which was conducted at grade ninth students of SMP Negeri 1 Gaung. The samples consisted of 48 students. In collecting the data, the researcher used a test that is formed in the multiple-choice test. After conducting the research, it found the tobserved was 7.14, which was higher than the ttable score in the degree of significance 1 % and 5% (2.687<7.12>2.410). It means that the alternative hypothesis (H1) of the research is accepted and the null hypothesis (Ho) was rejected. In other words, the use of CIRC method toward students reading comprehension of descriptive text at grade ninth of SMP Negeri 1 Gaung is effective.